Pellet reduction properties under different blast furnace operating conditions - Leimalm, Ulrika (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2006)
One of the aims of modern blast furnace (BF) ironmaking is to reduce coke consumption. One way is to increase the injection of reduction agents, such as pulverized coal. An increase in pulverized coal injection rate (PCR) will affect the blast furnace process and the conditions for iron oxide reduction. Changes in PCR influence the composition of the ascending gases and the in-furnace temperature isotherms. The performed tests involve full-scale, pilot and laboratory investigations. Raw material sampling of, among other things, pellets was carried out during a period of fluctuations in the hot metal Si content at the SSAB BF No. 3 at Luleå. Although differences in pellet low-temperature reduction disintegration and the high-temperature breakdown were observed, the reduction behaviours during blast furnace simulation tests were almost identical. Differences in the hot metal Si content in a production blast furnace were difficult to correlate to raw material properties, since the process conditions were changed in order to control the heat level of the blast furnace. Tests in the LKAB Experimental Blast Furnace (EBF) were carried out under different pre-set process conditions. Injection of high-volatile (HV) coal resulted in a higher reduction potential in the ascending gas due to a higher H2 content and an increased shaft temperature compared to operation with low-volatile (LV) coal. A higher pellet reduction degree was attained in pellets taken out with the upper shaft probe during operation with the HV coal compared to injection of the LV coal. The differences receded through the shaft and no differences in pellet reduction degree that can be correlated to the pre-set process conditions were observed in samples taken out with the lower shaft probe. However, differences in the pellet texture were observed. For the HV coal, a higher pellet strength but also an increase in generation of Femet fines, was observed compared to operation with the LV coal. Different Femet textures were observed in the pellet depending ...